Tariffs and the East Asian financial crisis - Bora, Bijit; Neufeld, Inge Nora (United Nations, 2001)
This study examines the role of tariffs during the East Asian financial crisis and finds that there is a role of tariffs when it comes to fighting the negative impact of a financial downturn. The first section reviews the pre-crisis trade environment, examining economic performance and main policy developments. Next, this paper examines the management and adjustment measures taken in the wake of the financial downturn. This is followed by a detailed analysis of the Affected-5's response in terms of their tariff policy. Finally, the study concludes with an identification of lessons about the role of tariffs.--Publisher's description.
Keywords: World Trade Organization; Geschichte 1997-1998; ARANCEL ADUANERO - EXTREMO ORIENTE; CRISIS FINANCIERA - EXTREMO ORIENTE; Crises boursières - Asie orientale; Crises financières - Extrême-Orient; Crisis financieras - Asia Oriental; EAST ASIA; ECONOMIC REFORM; FINANCIAL CRISIS; Financiële crises; INDONESIA; Internationale handel; Invoerrechten en uitvoerrechten; MALAYSIA; PHILIPPINES; REPUBLIC OF KOREA; TARIFFS; THAILAND; TRADE AGREEMENTS; TRADE LIBERALIZATION; TRADE POLICY; Tarif douanier - Asie orientale; Tarif douanier - Extrême-Orient; Tarifas - Asia Oriental; Welthandel; Financial crises -- East Asia; Financial crises -- Southeast Asia; Tariff -- East Asia; Tariff -- Southeast Asia; Außenhandelspolitik; Währungskrise; Protektionismus; Wirtschaftskrise; Asie orientale - Conditions économiques - 1997-...; Extrême-Orient - Politique commerciale; Politique commerciale - Asie orientale; Ostasien; Südostasien; East Asia -- Commercial policy; Southeast Asia -- Commercial policy; Asiatisch-Pazifischer Raum